Together We Can Make It Work! Toward a Design Framework for Inclusive and Participatory City-Making of Playable Cities - Slingerland, Geertje; Lukosch, Stephan; Hengst, Mariëlle den; Nevejan, Caroline; Brazier, Frances (Frontiers in Computer Science, 2020)
Making it work together can be challenging when various stakeholders are involved. Given the context of neighborhoods and cities specifically, stakeholders values and interests are not always aligned. In these settings, to construct long-term and sustaining participatory city-making projects, to make it work together, is demanding. To address this challenge, this paper proposes a design framework for inclusive and participatory city-making. This framework is inspired by the playable city perspective in that it endorses an open, exploratory, and interactive mindset of city actors. An extensive literature review on approaches taken for playful and participatory interventions in local communities provides the foundations for the framework. The review brings forward four pillars on which the framework is grounded and four activities for exploration of the design space for participatory city-making. A case study from The Hague (NL) is used to demonstrate how the framework can be applied to design and analyze processes in which city stakeholders together make it work. The case study analysis complements the framework with various research methods to support researchers, urban planners, and designers to engage with all city stakeholders to create playful and participatory interventions, which are inclusive and meaningful for the local community. The research contributions of this paper are the proposed framework and informed suggestions on how this framework in practice assists city stakeholders to together make it work.